Megymenum distanti, a new remarkable species of the Dinidoridae subfamily Megymeninae (Hemiptera: Heteroptera: Dinidoridae) from India - Kocorek, Anna; Ghate, Hemant (Zootaxa, 2012)
Megymenum distanti, a new species of the dinidorid subfamily Megymeninae, is described from India and is comparedwith M. affine and M. brevicorne. It is the sixth species of this genus known from India. Remarks on the habitat, wherethe type material was collected, photographs of the host plant and a brief description of all instars are provided. This species is of a different color as an adult and as nymphs, a situation which is unusual.